Between the local and the global: The pedagogical experience of Raúl Hestnes Ferreira - Saraiva, A. (2021)
This article intends to emphasize Raúl Hestnes Ferreira’s (1931-2018) merits in three fields: architectonic practice, pedagogical experience, and architectural research. His remarkable and important contribution to Portuguese architecture was recognized by Coimbra University in 30th of September 2007, when he was awarded with the degree of Doctor Honoris Causa. He is an honorary member of Portuguese Institute of Architects (2010) and he owns a renown and awardwinning professional practice. The article addresses Ferreira’s experiences in Scandinavia, in the late 1950s, where he looked at Alvar Aalto’s architecture, and in the USA, in the early 1960s, where he did a master in Pennsylvanian University and collaborated with Louis Kahn. Ferreira’s research focused on Cassiano Branco’s production, where he reflected about the relationship between ideology and architecture in the 1930s and the role of engineers in the change of the Lisbon image after that decade.